Effect of intravenous fluid supplementation in healthy term neonates with non-hemolytic hyperbilirubinemia: A randomized controlled trial - Sarvi, Meenakshi; Patil, Shailesh S; Desai, Arunkumar (Indian Journal of Child Health, 2018)
Objective: The objective of this study was to evaluate the effect of intravenous fluid supplementation in healthy term neonates with non-hemolytic hyperbilirubinemia receiving phototherapy. Study Design: Randomized controlled trial conducted in a tertiary level neonatal care unit of a teaching institute in North Karnataka. Methods: A total of 60 healthy term neonates with non-hemolytic hyperbilirubinemia (total serum bilirubin [TSB] >15 mg/dL [256 ?mol/L]–